Aroha ki ō tātou kaimahi = Love to our workers : rigorously imagining the conceptual process of Aotearoa workplace design : a thesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, Wellington, New Zealand - Stokes, Georgina (Massey University, 2020)
We are currently within a time where our sociocultural operating systems of spatial design are in a state of flux. What it means to work in an interior workplace environment is changing rapidly. In 2015 Nesta, the global innovation foundation, appealed for worldwide spatial design contribution to their future scoping investigation about alternative workplace design methods. Nesta's study encouraged thinking beyond traditional systems of work to prove that a globalised methodology will no longer be the answer to designing our future workplaces. Aroha ki ō Tātou Kaimahi was thus formulated as an Aotearoa-specific offering to Nesta's investigation. Through a critique of our New Zealand Government workplace design guidelines, I question how our workplaces can better become an expression of Aotearoaness; our community values, our indigenous culture, traditions and sense of place. This approach necessitates interrogation of the conceptual processes involved in designing an interior workplace through learnings of site-specific histories from tangata whenua. In this research project, I apply a Te Ao Māori perspective to rigorously re-imagine the spatial experience of traditional workplace environments through an experimental drawing practice. In doing so, I argue this rigorous re-imagining contributes to the discourse of design decolonisation in Aotearoa. The core innovation of this offering is the translation of archival mātauranga Māori systems of spatial mapping, concepts of cultural spatial sensibility and phenomenological Oceanic architectural methods into a workplace design context. This approach offers a resourceful process of explorative conceptual cultural-spatial thinking to current spatial design practice in the form of an educative and speculative set of drawings; strategic plots and dreamscapes. Furthermore, this research encourages continued support and learning for future Aotearoa designers, architects and placemakers between our local workplaces, our kaimahi and our Māori kaupapa.
Some copyrighted Figures are re-used under the "fair use" principle for the purpose of criticism or review.
Keywords: Māori Masters Thesis; 451110 Te whakaharatau me te whakahaere hoahoa o te Māori (Māori design practice and management)